Uji Kevalidan dan Kepraktisan Penggunaan Media Pop-Up Book Digital Berorientasi Kearifan Lokal Makanan Khas Kediri Dalam Pembelajaran Teks Prosedur Kelas 3 Sekolah Dasar - Syifa’, Zakiyyah Ainus; Istiq’faroh, Nurul; Amanda, Widya (Tumoutou Social Science Journal, 2026)
Indonesian language learning at the elementary school level often faces challenges due to students' low understanding of procedure text structures, resulting from the use of less varied learning media. This study aims to develop and test the validity and practicality of digital Pop-Up Book media oriented toward the local wisdom of Kediri’s traditional food. By integrating local culture, it is expected that the learning process will become more contextual, engaging, and meaningful for third-grade students. The research method employed is Research and Development (R&D), adopting the ADDIE development model which includes Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted during the even semester of the 2025/2026 academic year. Data collection instruments included observation sheets, documentation, and user response questionnaires measured using a Likert scale. This media was designed based on the TSSJ principles, blending textual elements, static images, and interactive three-dimensional animations to visually clarify each stage of the procedure text. The results of the study indicate that the digital Pop-Up Book media themed on local wisdom meets the criteria for being highly practical and feasible for use in teaching and learning activities. Based on data analysis, the average percentage score from teacher responses was 96.35%, while student responses reached 93.75%. These findings indicate that the use of digital-based interactive visual media is not only effective in improving cognitive understanding of procedure text structures but also capable of fostering student interest and appreciation for their local culture. This media represents a learning innovation highly relevant to current digital education needs.